How UV light lowers the conductivity of SrTiO3 by photochemical water splitting at elevated temperature. Issue 6 (22nd February 2022) - Viernstein, Alexander; Kubicek, Markus; Morgenbesser, Maximilian; Huber, Tobias M.; Siebenhofer, Matthäus; Fleig, Jürgen
Abstract : Explaining the impact of oxygen incorporated into SrTiO3 single crystals in strongly reducing H2 /H2 O containing atmospheres under UV illumination at 350 °C. Abstract : Nominally undoped SrTiO3 single crystals were illuminated by UV light at 350 °C in oxidizing as well as reducing atmospheres. In N2 /O2 atmospheres, UV irradiation enhances the conductivity of SrTiO3 by several orders of magnitude. In dry H2 atmosphere UV exposure leads to the opposite conductivity effect, i.e., above band gap energy illumination surprisingly lowers the conductivity. This is discussed in the framework of a defect chemical model. We show that a shift in defect concentrations due to UV-driven oxygen incorporation from the gas phase into the oxide is the main cause of the measured conductivity changes. A model is introduced to illustrate the thermodynamic and kinetic drivers of the processes under UV irradiation. Noteably, in reducing H2 /H2 O atmospheres, the incorporation of oxygen into the investigated oxide under UV light takes place via water splitting. Owing to the predominant electron conduction of SrTiO3 in equilibrium with H2, oxygen incorporation upon UV and thus an increase of the oxygen chemical potential leads to a decrease of the majority electronic charge carrier, here electrons, which lowers the conductivity under UV irradiation.